Energy requirements for growth in male and female Saanen goats - Almeida, A. K. [UNESP] (2015)
The aim of this study was to investigate the energy requirements of female and intact and castrated male Saanen goats. Animals were randomly assigned to 1 of 2 experiments designed to investigate the energy requirements for maintenance and gain. To determine the maintenance requirements, 85 goats were used (26 intact males, 30 castrated males, and 29 females) with an initial BW of 30.3 ± 0.87 kg. Thirty goats (8 intact males, 9 castrated males, and 13 females) were slaughtered to be used as the baseline group. The remaining goats were assigned in a split-plot design using a 3 × 3 factorial arrangement (3 sexes—intact males, castrated males, and females—and 3 DMI levels—ad libitum and restricted fed to 75 or 50% of the ad libitum intake). The NEg was obtained using 65 goats (20 intact males, 22 castrated males, and 23 females) fed ad libitum in a completely randomized design. Eight intact males, 9 castrated males, and 13 females were slaughtered at 30.5 ± 1.53 kg BW. Seventeen goats (6 intact males, 6 castrated males, and 5 females) were slaughtered at 38.1 ± 0.49 kg BW. The remaining goats were slaughtered at 44.0 ± 0.50 kg BW. The NEm did not differ between the sexes (P = 0.59; 258.5 kJ/kg0.75 BW), resulting in a ME for maintenance of 412.4 kJ/kg0.75 BW. The estimated energy use efficiency for maintenance was 0.627. During the growth phase, NEg differed between the sexes (P < 0.001); intact males, castrated males, and females showed an average NEg equal to 15.2, 18.6, and 22.7 MJ/kg of empty weight gain, respectively. The energy requirements for growth differed between the sexes. The difference was found to be due to distinct NEg and partial efficiency of ME utilization for growth in intact and castrated males and females during the late growth phase. This study may contribute to adjustments in feeding system energy recommendations regarding the NEm and NEg found for goats during the late growth phase.